Effect of organic and integrated farming on carotenoid and tocopherol content of apricot fruits - Hussein, G. D.; Bánáti, D.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2011)
In modern and healthy diets antioxidants play an important role providing natural defence against serious diseases. Therefore it is recommended to include fruits and vegetables having high antioxidant capacity in daily diet in a due course. Apricot is one of the fruits receiving an increasing attention in this field. This study was conducted to investigate the composition and content of fat-soluble carotenoids and tocopherols in different varieties of apricot using recently developed liquid chromatographic methods. Also it was aimed to compare organic and integrated farming in their effect on carotenoid and tocopherol content of the fruits. The results showed that apricot fruit are rich in vital carotenoids and bioactive tocopherols with significant variation between different varieties. The organic farming had favourable effect on the level of the major carotenoids and depending on variety this technology either increases or does not have significant influence on vitamin E content.